The Contribution of Exposure Frequency to English to Speaking and Writing Performance of EFL Learners at Junior High School in Indonesia - Hajriana Arfah; Ahmad Zam Zam (VELES Voices of English Language Education Society, 2017)
This study was aimed at describing the contribution of exposure frequency to English (EFE) to speaking and writing English as a foreign language (EFL) learners in bilingual class setting of a state junior high school in East Lombok, which has been implementing bilingual principles (English-Indonesia) of Mathematics and Natural Science. This research is ex-post facto with correlation design. The samples were systematically selected by choosing even number of the student lists, which involved forty-six of ninety-three students of eight grade in academic year 2011/2012. Data were analyzed with regression. The calculation was done at 5% significant level.This research discovered that (1) there is a significant correlation between exposure frequency to English language and speaking performance of the students in bilingual classes by R value of  .555 with probability of  .00; (2) there is significant correlation between exposure frequency to English and writing performance by R value of  .78 with probability of  .00; (3) the EFE significantly contribute to writing performance with R Square value of  .609 (60.9%); and (4) it also contribute.309 (30.9%) the studentsâ€™ speaking performance.